Synthesis, characterisation and anti-corrosion screening of ni(ii) n-butylmethyl dithiocarbamate and ni(ii) n-ethylbenzyl dithiocarbamate / Nor Farah Hida Othman - Othman, Nor Farah Hida (Faculty of Applied Sciences, 2017)
Two dithiocarbamates complexes which are Ni(II) N-butylmethyl dithiocarbamate, Ni[BuMedtc]2 and Ni(II) N-ethylbenzyl dithiocarbamate Ni[EtBenzdtc]2 were successfully synthesised using in situ method. Both complexes were characterised by FT-IR and UV-Vis spectroscopy, gravimetric analysis, molar conductivity, melting point and X-ray Crystallographic analysis. From IR spectroscopy, the important stretching bands which are v(C:.:.::.:::N) and v(c:.:.:.:.:.:.:·s) were appeared in the range of 1508-1518 cm-1 and 948-967 cm-1 respectively. The absence of v(N- H) bands after complexation in spectra of both complexes proved that the formation of complexes have been take place. For UV-Vis spectroscopy, there are absorption peak observed in the Ni[BuMedtc]2 and Ni[EtBenzdtc]2 at 325 nm and 330 nm respectively. It is indicated to the n-----+n* transitions. At more than 400 nm, there was absorption peak appeared which is indicated to the d-d transitions of Ni(II) complexes. The melting points of both complexes were higher than 300 °C. The molar conductivity showed that Ni[BuMedtc]2 and Ni[EtBenzdtc]2 were non-electrolyte. The gravimetric analysis showed the percentage of Ni(II) in Ni[BuMedtc]2 was 7.5% meanwhile in Ni[EtBenzdtc]2 was 5.98%. For X-ray crystallographic analysis, only Ni[BuMedtc]2 that was successfully produced single crystal that suitable for this analysis. The results obtained showed that Ni[BuMedtc]2 is four-coordination tetrahedral geometry and adopted to hexagonal system with the crystal parameter: a = 25.544(10) A, b = 25.544(10) A, c = 7.018(5) A, a= 90° , JJ= 90°, 5= 120° and Z = 9. The corrosion inhibition study showed that C2 has higher corrosion inhibitor efficiency than Ni[BuMedtc]2. From this study also showed that the inhibitor efficiency increased as the concentration of inhibitor increased.